2019
DOI: 10.1093/jxb/erz200
|View full text |Cite
|
Sign up to set email alerts
|

The initiation of bud burst in grapevine features dynamic regulation of the apoplastic pore size

Abstract: Molecular modelling, histochemistry, and micro-computed tomography reveal that the apoplastic pore size is dynamically regulated during bud burst in grapevine, and associated with oxygenation of the meristematic core.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 39 publications
0
18
0
Order By: Relevance
“…Our earlier studies have indicated that oxygen and ethylene signalling ( Meitha et al , 2015 , 2018 ) and cell–cell transport ( Signorelli et al , 2020 ) may have key regulatory roles in bud development. In addition, we have reviewed the role of cell cycle regulation as a master or slave of dormancy transitions ( Velappan et al , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our earlier studies have indicated that oxygen and ethylene signalling ( Meitha et al , 2015 , 2018 ) and cell–cell transport ( Signorelli et al , 2020 ) may have key regulatory roles in bud development. In addition, we have reviewed the role of cell cycle regulation as a master or slave of dormancy transitions ( Velappan et al , 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…This was consistent with the hypothesis that water availability was an important variable affecting bud burst kinetics in single-node cutting experiments. It is well documented that quiescent buds are isolated to prevent dehydration during winter, particularly through the restriction of aquaporin activity, plasmodesmata conductance, and apoplastic conductivity [6][7][8][9][10]. For water to have a direct effect on bud burst, it needs to be transported to the bud after transferring the single-node cutting to the seedling tray.…”
Section: Resultsmentioning
confidence: 99%
“…In terms of GWC, 85% of FC in our system represented 0.94 g water •g soil −1 and 100% of FC was 1.11 g water •g soil −1 . Several earlier studies have illustrated the regulated changes in free and bound water [10], in the activity of aquaporin transporters [6,11], the role of plasmodesmata in dormancy transitions of perennating buds [7], the expansion of apoplastic connectivity upon bud burst [9], and the change dynamics in moisture content in the bud across the season [11]. The fact that water has a strong effect on bud burst in explant further supports the importance of those biological processes controlling water content in the bud, such as plasmodesmata regulation, aquaporins activity, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, grapes are considered one of the most economically important and vital fruit species and grown in almost 100 countries. Grapes are consumed in different forms, as fresh, dried (raisins), and processed food and beverages (juices and soft drinks) ( Signorelli et al, 2019 ). The current climatic anomalies and scenarios are a threat and can lead to unpredicted and urgent provocations to the grapevine’s traditional cultivation ( Leolini et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%